My first Patient in a World of his own, so near yet so distant - Khan, U. T. (Balint Journal, 2012)
This experience is about a medical student meeting his very first patient, an elderly person. Not knowing what to expect, he starts his excitement-filled journey juggling different, and often conflicting, emotions towards himself, the patient, and his family. The medical student explores the constant struggle of life faced by his patient and in particular, his carer – the wife.I met John as part of a module during my first year of medical school. John is now 95 years old and suffers from Alzheimer’s Disease. Every time I would go and visit him, he would sit quietly in the chair whilst I conversed with his wife. It was difficult to talk to him since, as a consequence of his Alzheimer’s, he had poor memory and difficulty in conversing.The thing that struck me most was the almost slaking effect my visits had on these conversation-starved individuals. Most of John’s friends were no longer alive, and their children were busy in their own life to dedicate round-the-clock care to him although they came regularly to check on their parents. So the two sat in exactly the same position whenever I visited them, and it would seem my visits were the only thing that broke that monotony. The experience opened my eyes to the desperate condition of geriatric patients in society. John was primarily cared for by his wife and I realised how important her role was in providing symptomatic relief to her husband despite the fact that she was not much younger than him.This highlights the stark reality and plight of most elderly nowadays. The elderly population is on the rise in UK 1 and they are increasingly becoming lonely as they age. This has serious repercussions as they are left on their own to cope with their diseases. The budgetary constraints in health budget are likely to make the situation worse.This being my very first exposure of any kind with patients was initially uncomfortable, but looking back, I can confidently say that the experience was, despite being challenging, hugely informative and formative at the same time. John and his wife helped me see the importance of a durable relationship between husband and wife, the value of love. I saw them interlocked in a relationship which consisted of mutual respect, love and care; a relationship that stood the test of time.